Evaluating Angiotensin Converting Enzyme (Ace) Gene Polymorphism as a Biomarker for predicting Acute Coronary Syndrome - Ritham (Thapar Institute of Engineering and Technology, 2025)
Background: Acute Coronary Syndrome (ACS) is still one of the most dangerous forms of cardiovascular disease, with a high rate of death and illness around the world. High blood pressure, diabetes, and dyslipidemia are all common risk factors that make people more likely to get sick. However, more and more evidence shows that geneticpredisposition plays a very important role in the development of ACS. TheAngiotensin-Converting Enzyme (ACE) gene insertion/deletion (I/D) polymorphismis one of these genetic factors. It affects plasma ACE levels and may alter the riskof getting heart attack by impacting vascular tone, thrombosis, and the progressionof atherosclerosis. Purpose: The goal of this study is to analyze the link between ACE I/D polymorphismandtherisk of ACS, especially in the North Indian population, and to see howit relates todifferent clinical parameters. The main objective is to find out if this polymorphismcan be used as a predictive genetic biomarker that can help with early riskstratification and possible clinical decision-making. Experimental Design: A case-control study was done with ACS patients and healthy controls fromNorthIndia who were the same age and sex as the patients. We took genomic DNAfromperipheral blood samples and used Polymerase Chain Reaction (PCR) technique todetermine the ACE I/D polymorphism. Statistical tests were used to look at thedistribution of genotypes (II, ID, DD) and allele frequencies. We used the right statistical tools to figure out if there were any links between genotypes and important clinical factors like blood pressure, BMI, smoking history, and diabetes status etc. Results Upon statistical analysis, no significant correlation was found between the ACEI/Dpolymorphism and the risk of Acute Coronary Syndrome. However, age-dependent risk, presence of co-morbidities such as diabetes and hypertension was significantly found to be associated with the DD genotype. The risk allele negatively impacted the Intra Ventricular Septal thickness of the heart and caused greater vascular damage. These findings underscore the role of genetic, metabolic, and structural markers in ACS risk assessment.
Keywords: Angiotensin; Enzyme; Coronary Syndrome; Gene Polymorphism; Genomic DNA